Assessing Interface Dependency Complexity in Components based Software Systems (CBSS) (Don Bosco Institute of Technology Delhi Journal of Research, 2025)
Systems with high complexity typically exhibit a balanced combination of order  and disorder, characterized by the coexistence of randomness and regularity. In  component-based software engineering, each component contributes to overall  system complexity through its inherent constraints, interaction mechanisms with  other components, and the degree of customizability it supports. As software  systems grow in scale and interconnectivity, understanding and managing such  complexity becomes critical to ensuring system reliability, maintainability, and  quality. Measuring system dependency and interaction complexity provides valuable  insights into potential design weaknesses and helps assess software quality at both  component and system levels. Complexity metrics play a crucial role in enabling  objective comparison across different software systems by applying standardized  measurement frameworks. Existing complexity measures, however, often focus  primarily on internal code structure, overlooking the significance of component  interfaces that govern communication, data exchange, and functional coordination. The author has pointed out a novel interface complexity metric for software  components in the study. Based on the quantity, kind, and structural features of  interface methods and attributes that a component exposes, the suggested metric  measures complexity. Factors such as method signatures, parameter types, data  dependencies, access constraints, and interaction frequency are considered to  capture the true interaction burden imposed by component interfaces. By focusing  on interface-level complexity, the metric provides a more accurate representation  of component interdependencies and their impact on overall system behaviour.  The proposed approach supports improved software design evaluation, facilitates  early detection of architectural vulnerabilities, and aids developers in enhancing  modularity, reusability, and long-term system quality.
Keywords: Software Complexity, Software metric, Information flow, Traditional metrics, CBSS